2020
DOI: 10.21608/ejvs.2020.20965.1143
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Age Distribution of Toxoplasma gondii in Milk of Naturally Infected Animal Species and Dairy Samples

Abstract: RIMARY infection by Toxoplasma gondii is habitually food borne and ingestion of foods with animal origins is measured as a risk factor. The current survey was performed to assess the seasonal and age distribution of T. gondii in diverse kinds of raw milk and traditional dairy products. Three-hundred and seventy raw milk and traditional dairy samples were collected and subjected to DNA extraction. B1 specific gene of T. gondii was perceived by means of the molecular technique. Eighteen out of 370 (4.86%) studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The findings in this study revealed that the T. gondii DNA-positive milk samples belonged to the summer sampling period, and the frequency of each positive milk sample was 20% for June, July and August. The summer and autumn seasons are considered an important predisposing factor for the incidence of T. gondii due to the grazing of animals in pasture and the high cat population shedding T. gondii oocysts (Dubey et al 2014;Alipour Amroabadi et al 2020). Several authors demonstrated the long-term survival of T. gondii cysts in the cheese samples obtained from the milk experimentally infected with this agent (Hiramoto et al 2001;Camossi et al 2011;Dubey et al 2014;Costa et al 2020;Ranucci et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings in this study revealed that the T. gondii DNA-positive milk samples belonged to the summer sampling period, and the frequency of each positive milk sample was 20% for June, July and August. The summer and autumn seasons are considered an important predisposing factor for the incidence of T. gondii due to the grazing of animals in pasture and the high cat population shedding T. gondii oocysts (Dubey et al 2014;Alipour Amroabadi et al 2020). Several authors demonstrated the long-term survival of T. gondii cysts in the cheese samples obtained from the milk experimentally infected with this agent (Hiramoto et al 2001;Camossi et al 2011;Dubey et al 2014;Costa et al 2020;Ranucci et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It was stated that the resistance of tachyzoites in cheese depends on changes in cheese pH, lactic acid bacteria (LAB) growth and salt concentration during the cheesemaking process and maturation period (Hiramoto et al 2001;Dubey et al 2014;Costa et al 2020;Ranucci et al 2020). There are limited data on the detection of T. gondii in cheeses (Alipour Amroabadi et al 2020;Costa et al 2020). The seroprevalence of T. gondii in T€ urkiye has been reported to range from 4% to 93.3% in cattle, from 4.6% to 99% in ewes and from 12% to 95% in goats (Karagenc et al 2005;Oncel and Vural 2006;Acici et al 2007;Mor and Arslan 2007;Yildiz et al 2009;Akca and Mor 2010;Cicek et al 2011;Leblebicier and Yildiz 2014;Yucel et al 2014;Celik et al 2016;Ozmutlu Cakmak and Karatepe 2017;Zhou et al 2017;Aktas and Aydin 2020), but no data are available on the presence of T. gondii tachyzoites or parasite DNA in milk and milk products from naturally infected animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross‐sectional study was conducted from April to September 2020. The sample size for the study was calculated using the following formula, assuming an expected prevalence of 25% and 15% of T. gondii in buffalo and cattle meat, respectively, based on previous studies (Alipour Amroabadi et al., 2020), with a desired absolute confidence level of 95% and a percent error of 5% (Motamed & Zamani, 2016). Based on these parameters, it was estimated that a total of at least 47 buffaloes and 97 cattle needed to be sampled: nbadbreak=Z1α/22×p0.28em(1p)d2$$\begin{equation*}n = \frac{{Z_{1 - \alpha /2}^2 \times p\;(1 - p)}}{{{{d}^2}}}\end{equation*}$$where P is the prevalence, α is the error rate, and d is the accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…gondii in buffalo and cattle meat, respectively, based on previous studies (Alipour Amroabadi et al, 2020), with a desired absolute confidence level of 95% and a percent error of 5% (Motamed & Zamani, 2016).…”
Section: Samplingmentioning
confidence: 99%